Cyclodextrin Metal–Organic Frameworks: A Green Metal–Organic Framework‐Cyclodextrin MOF: A Novel Multifunctional Material Based Triboelectric Nanogenerator for Highly Efficient Mechanical Energy Harvesting (Adv. Funct. Mater. 28/2021). (8th July 2021) - Hajra, Sugato; Sahu, Manisha; Padhan, Aneeta Manjari; Lee, In Sang; Yi, Dong Kee; Alagarsamy, Perumal; Nanda, Sitansu Sekhar; Kim, Hoe Joon
Abstract : In article number 2101829, Sitansu Sekhar Nanda, Hoe Joon Kim, and co‐workers demonstrate the application of cyclodextrin metal–organic framework (CD‐MOF), a green multifunctional material, to the electrifying layer of a multi‐unit triboelectric nanogenerator. The developed device exhibits outstanding power outputs along with stable operation. The fabricated device output is utilized for self‐powered biomechanical sensing and powering of numerous low‐power electronics through a capacitor and bridge rectifier circuit.